1999
DOI: 10.1108/00035599910263152
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion effects on the electrical performance of silver metal contacts

Abstract: In this work, commercial silver metal contacts welded on top of silver plated brass or brass substrates have been exposed to air rich in NaCl. Scanning electron microscopy and energy dispersive analysis of the exposed contact surfaces were performed to identify the corrosion byproducts on top of the silver contacts, suspending wafers, and welding materials. Surface corrosion products were mainly found to consist of small spherules of Cu-Zn or Ag-Cu compounds which cover the surface of the contact proper with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Several studies have been done on silver and copper corrosion and revealed that silver sulfide is the main corrosion product obtained when the silver is exposed to indoor and outdoor environments [2][3][4][5][6][7][8][9]. This corrosion film induces an insulating layer at the contact surfaces causing electrical failures on the devices.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been done on silver and copper corrosion and revealed that silver sulfide is the main corrosion product obtained when the silver is exposed to indoor and outdoor environments [2][3][4][5][6][7][8][9]. This corrosion film induces an insulating layer at the contact surfaces causing electrical failures on the devices.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable experience and a number of analytical techniques have been explored over the years concerning silver's tarnish and found sulphuration of silver caused tarnishing to occur (Fukuda and Fukushima, 1991; Vassiliou and Dervos, 1999; Mehan and Mansingh, 2000; Hindin and Fernandez, 2003). Tarnish means a darkening of the surface of silver and rendering it aesthetically unacceptable.…”
Section: Introductionmentioning
confidence: 99%